The Effect Of Collective Game-Based (CGB) And Spatial Ability On Students’ Vocabulary Mastery In English Learning - Mukarromah, Marwah (CV. ULIL ALBAB CORP, 2026)
Spatial ability is a crucial cognitive domain involving visualization, mental rotation, spatial perception, and orientation, and its role is increasingly acknowledged not only in STEM but also in language learning, particularly in vocabulary acquisition with spatial content. This study investigated the effect of the Collective Game-Based (CGB) approach and spatial ability on students’ vocabulary mastery in English. It examined whether CGB-based instruction outperforms conventional teaching and how spatial ability and gender relate to learning gains. A quantitative quasi-experimental design with pretest–posttest control groups was employed. The experimental group received vocabulary instruction through CGB activities integrating collaboration, digital/visual interaction, and contextual spatial vocabulary tasks, while the control group was taught using traditional methods. Vocabulary mastery tests and spatial ability measures were administered before and after the intervention. Data were analyzed using Wilcoxon tests to examine pre–post changes and independent t-tests to compare posttest scores between groups by gender. Results showed significant improvement in vocabulary mastery for the CGB group, but not for the control group. Male students achieved slightly higher gains, yet both males and females improved significantly, indicating that spatial ability is malleable and responsive to instructional intervention.